Relationship between plasma bubbles and density enhancements: Observations and interpretation. Issue 2 (19th February 2014) - Huang, Chao‐Song; Le, G.; de, O.; Roddy, P. A.; Hunton, D. E.; Pfaff, R. F.; Hairston, M. R.
Abstract Plasma bubbles are regions of depleted plasma density in the nighttime equatorial ionosphere. Plasma enhancements, also referred as plasma blobs, are regions where the plasma density is increased. It has not been well understood whether and how plasma enhancements are related to plasma bubbles. In this paper, we present the observations of plasma bubbles and enhancements by the Communication/Navigation Outage Forecasting System (C/NOFS) satellite during 2008 and 2009. In some cases, C/NOFS first detected plasma bubbles near the magnetic equator and then plasma enhancements at the same longitudes but at higher latitudes during subsequent orbits. In other cases, C/NOFS first detected plasma enhancements at off‐equatorial locations and then plasma bubbles near the magnetic equator at the same longitudes. It is also found that plasma enhancements existed just above plasma depletions. We propose a unified scenario to describe the evolution of plasma bubbles and the formation of plasma enhancements. In the proposed scenario, plasma enhancements can occur at different latitudes and altitudes during the early, intermediate, and late stages of the bubble evolution. This scenario provides a reasonable explanation of the observations.